Implementation Strategy of Tangerang Government University in Developing the Competency of Civil Servants in Tangerang City Government - Paramitha, Pradya; Silitonga, Mala Sondang; Sutrisno, Edy (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research was conducted to look for factors that influence and look for strategies for implementing Tangerang Government University in developing the competency of the Tangerang City Government civil servants. The method used is descriptive qualitative. Primary data was obtained from in-depth interviews with key informants and secondary data came from observations, books, journals and related regulations. The results of the research are the factors that influence the implementation of Tangerang Government University , namely vision and goals; scope and role; target audience and training substance; learning methods; branding and collaboration. Of the 6 factors influencing the implementation of Tangerang Government University, several obstacles were found, namely lack of motivation for ASN to change; limited human resources; application capabilities are not optimal; differences in thought patterns; limited budget. Recommended strategies that can be implemented are socializing Tangerang Government University , budget support; carry out continuous updates in the application; giving awards; create a mini corporate university.